Mesenchymal Stem Cells as a Prospective Therapy for the Diabetic Foot - Qinan Wu; Bing Chen; Ziwen Liang (Hindawi Limited, 2016)
The diabetic foot is a serious complication of diabetes. Mesenchymal stem cells are an abundant source of stem cells which occupy a special position in cell therapies, and recent studies have suggested that mesenchymal stem cells can play essential roles in treatments for the diabetic foot. Here, we discuss the advances that have been made in mesenchymal stem cell treatments for this condition. The roles and functional mechanisms of mesenchymal stem cells in the diabetic foot are also summarized, and insights into current and future studies are presented.